The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1152/ajpregu.00095.2008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic blockade of hindbrain glucocorticoid receptors reduces blood pressure responses to novel stress and attenuates adaptation to repeated stress

Abstract: Exogenous glucocorticoids act within the hindbrain to enhance the arterial pressure response to acute novel stress. Here we tested the hypothesis that endogenous glucocorticoids act at hindbrain glucocorticoid receptors (GR) to augment cardiovascular responses to restraint stress in a model of stress hyperreactivity, the borderline hypertensive rat (BHR). A 3-to 4-mg pellet of the GR antagonist mifepristone (Mif) was implanted over the dorsal hindbrain (DHB) in WistarKyoto (WKY) and BHRs. Control pellets consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 71 publications
7
31
1
Order By: Relevance
“…Consistent with previous reports (4,5,22,23), repeated exposure to restraint stress resulted in an adaptation of the HPA axis that was manifested as a habituation to stress-induced corticosterone secretion, as well as a mild but reliable hypersecretion of basal corticosterone (24,25). Our data demonstrate that AEA and 2-AG are divergently regulated by repeated stress, and independently contribute to distinct forms of HPA axis adaptation.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous reports (4,5,22,23), repeated exposure to restraint stress resulted in an adaptation of the HPA axis that was manifested as a habituation to stress-induced corticosterone secretion, as well as a mild but reliable hypersecretion of basal corticosterone (24,25). Our data demonstrate that AEA and 2-AG are divergently regulated by repeated stress, and independently contribute to distinct forms of HPA axis adaptation.…”
Section: Discussionsupporting
confidence: 92%
“…To this point, it has been indicated that chronic stress does not have an effect on BP (Scheuer et al 2007;Bechtold et al 2009;Scheuer 2010) and nesfatin-1 increases BP Samson 2009, 2010;García-Galiano et al 2010). Yosten and his colleagues have showed that intracerebroventricular nesfatin-1 administration increases BP (Yosten and Samson 2009) and this effect of nesfatin-1 occurs via sympathetic system activation (Yosten and Samson 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular responses occur after acute and chronic stress, which can increase the risk of hypertension and cardiovascular diseases (Bechtold et al 2009). Nesfatin-1 can control appetite in a different pathway than leptin and increases insulin secretion by activation of L-type Ca 2+ channels in pancreatic islet beta cells (Cowley and Grove 2006;Nakata et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of stress have been applied, such as emotional stimuli, psychosocial stress, immobilization stress, food deprivation and electric stimuli, air jet noise, flashing lights, cold, and interaction of members of a social group as they compete for food and water (Henry 1975;Friedman and Dahl 1975;Papanek et al 1991;Henry et al 1993;Tucker and Hunt 1993;Bechtold et al 2009). …”
Section: Psychosocial and Environment-induced Hypertensionmentioning
confidence: 99%